KUALITAS LABA: INVESTMENT OPPORTUNITY SET DAN KOMITE AUDIT - Kixi Oktapiani; Endang Ruhiyat (Jurnal Ilmiah Akuntansi Universitas Pamulang, 2019)
This study aims to test and empirically prove the Effect of Investment Opportunity Set and Audit Committee on Profit Quality. The locus of this research is the Property and Real Estate companies listed on the Indonesia Stock Exchange in 2014-2017 consisting of 61 companies. Samples were taken using a purposive sampling technique that produced a sample of 30 companies with observations over 4 (four) years, so that the total observation data was 120 audited financial statements. The data analysis method uses descriptive statistical analysis and multiple linear regression analysis, and hypothesis testing with a significance level of 5%. The test equipment used was the SPSS version 22 program. Based on the results of the hypothesis test, the investment opportunity set results do not affect earnings quality and the audit committee has a significant effect on earnings quality, while simultaneously shows that investment opportunity set and audit committee have a significant effect on earnings quality.